2019
DOI: 10.3126/njb.v7i1.26947
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol Extract of Choerospondias axillaris Fruit Pulp Enhances Haematological Parameters in Oncorhynchus mykiss Cultured in Nepal

Abstract: The present outdoor experiment was carried out to evaluate the effect of dietary supplementation of lapsi Choerospondias axillaris (Roxburgh, 1832) on haematological parameters in rainbow trout Oncorhynchus mykiss in Nepal. The lapsi fruits were obtained from local market of Kathmandu. The feeding trail was conducted for 90 days. About 270 trout with similar body weight (5±1g) were distributed randomly at the rate of 15 fishes per cage (1m3) into 18 cages placed in raceway pond. Six practical diets containing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…However, the species has also been domesticated and introduced in freshwater lakes and large rivers of Nepal, Asia, and worldwide. Recently, various mass mortalities have been reported in the Nepalese aquaculture system [ 21 ], and the use of immunostimulants is a suggestible alternative to antibiotics in this species.…”
Section: Introductionmentioning
confidence: 99%
“…However, the species has also been domesticated and introduced in freshwater lakes and large rivers of Nepal, Asia, and worldwide. Recently, various mass mortalities have been reported in the Nepalese aquaculture system [ 21 ], and the use of immunostimulants is a suggestible alternative to antibiotics in this species.…”
Section: Introductionmentioning
confidence: 99%
“…Earlier studies also demonstrated the use of total flavonoid content (possessing good antioxidants) of C. axillaris extract for the treatment of cardiovascular diseases in clinic (Li et al, 2013). Studies have also reported the use of C. axillaris in aquaculture over drugs and antibiotics as the drug causes several side effects to the consumer (Shakya and Labh, 2019). The methanol extract of C. axillaris has been demonstrated to have good cytotoxic activity against breast cancer cells, suggesting that the extract might have great potential as an anti-cancer agent.…”
Section: Discussionmentioning
confidence: 95%